Effect of feedstock preparation and forming temperature to the characteristics of green compacts - Rahman M.M.; Nor A.M. (2023)
This paper presents the outcomes of an experimental investigation on the effect of feedstock preparation to the mechanical properties and microstructures of green compacts formed at above ambient temperature. A lab-scale uni-axial die compaction rig was designed and fabricated which enabled the powder forming at elevated temperature. Iron powder ASC 100.29 was mechanically mixed with different quantity of zinc stearate for 10, 30, and 60 minutes, respectively. Green compacts were generated by forming the prepared feedstock at room temperature and 180°C through simultaneous upward and downward axial loading. The defect-free green compacts were subsequently characterized for their physical and mechanical properties and their microstructures were evaluated. The results revealed that the characteristics of green products were affected by feedstock preparation as well as forming temperature. From this study, the suitable zinc stearate content, mixing time, and forming temperature were identified for the generation of high quality green compacts through warm forming route. © (2014) Trans Tech Publications, Switzerland.